Influence of landing quadrant on elliptical orbit and its realtion to release parameters of the hammer throw - Treacy, A.; Konz, S.; Leigh, S. (ISBS Proceedings Archive (Michigan), 2021)
Hammer throw official distance is determined by the velocity, angle, and height of the hammer at release, which is regulated by the acceleration arc of the hammer during the turns. This study aimed to examine the influence of position variables describing the elliptical orbit during each turn on the official distance and the release parameters. Competitive hammer throws from 35 athletes (17 men and 18 women) were digitized to obtain 3-D coordinates of the thrower and the hammer throughout the throw. Multiple regression models indicate that hammer positioning during turns 1 and 2 accounts for the greatest variance in the official distance. Male throwers use the acceleration arc to regulate the release angle throughout the throw, whereas female throwers use the acceleration arc to regulate both release velocity and release angle throughout the throw.